Desenvolvimento de métodos analíticos e de formulações para estatinas - Taizia Dutra Silva (2009)
The statins are hypolipemic drugs used in the control of hypercholesterolemia. Simvastatin and lovastatin, low water soluble drugs and soluble sodium pravastatin are among the mostprescribed statins for the reduction of cholesterol. In this study two methods were developed and validated for the determination of these statins. A reverse phase high performance liquid chromatographic method was developed using a C-8 column, mobile phase composed ofacetonitrile: 0.1% phosphoric acid (65:35), 1.0 or 1.5 mL/min flow rate, column oven 30 ºC and UV detection 238 nm. A second order ultraviolet derivative spectrophotometric method was developed at l 247 nm using methanol. Both methods demonstrated to be selective, precise and accurate for the statins determination. A tablet simvastatin formulation was developed by means of a solid dispersion using the polymers PEG or PVP. Simvastatin tablets dispersions using PVP showed to be heterogeneous regarding the quality control routine tests. Simvastatin tablets dispersions using PEG showed good results for the weightdetermination, content uniformity and dissolution and met the requirements according to the Brazilian Pharmacopeia and USP32 specifications. In vivo tests using mice submitted to a hyperlipemic diet were performed using simvastatin in different forms: (a) simvastatin, (b)powder solid dispersions with PEG, (c) tablets solid dispersions with PEG, and (d) Zocor® tablets. The in vivo results showed a great variability in the experiment regarding the cholesterol reduction for all groups tested, hence, were not conclusive.